Shrinking mouse - Hutchins, Pat, 1942- (New York : Greenwillow Books, 1997)
Four animal friends notice that the size of distant objects seems to change depending on the location and movement of the viewer.
1.3
K-3
Keywords: Size -- Fiction; Animals -- Fiction; Visual perception -- Fiction; Size -- Fiction; Animals -- Fiction; Perception -- Fiction; Size -- Fiction; Animals -- Fiction; Visual perception -- Fiction